HOLOCENE LACUSTRINE SEDIMENTATION PATTERNS ON LORI PLATEAU (SOUTH CAUCASUS) - Fedorov, Grigory; Sadokov, Dmitry; Rudakov, Vsevolod; Fedorova, Irina; Ghazaryan, Larisa (International Multidisciplinary Scientific GeoConference SGEM, 2024)
This study provides a characterization of the Holocene sedimentary processes in Lake Urasar (Lori plateau, Armenia). Lake Urasar is less than 0.1 sq. km with 8.5 m max. depth. 2 m -long sediment core was retrieved by using peat corer in the deepest part of the lake during summer 2023. Obtained core was a subject for detailed lithological description and XRF-scanning. Three lithological units are identified in the sediment sequence reflecting different sedimentation patterns. Unit 1 (200 - 164 cm) characterized by frequent changes in the chemical elements concentrations and reflects sensitivity to the regional climate changes, which had been expressed as shifts in the eolian input rate, and surface soil fixation. Decrease of Fe and Ti values with less pronounced regular oscillations can be seen upcore in the Unit II (163 - 62 cm), which might be a clue for a decreased mineragenic input (for example, in the course of forest expansion and / or montane-steppe soil formation). Geochemical characteristics of the muddy uppermost deposits of Unit III reflect repeated disturbance and mixing.